PENGARUH KARAKTERISTIK PERUSAHAAN PADA LUAS PENGUNGKAPAN SUKARELA DAN IMPLIKASINYA TERHADAP ASIMETRI INFORMASI - Damayanti, Diah Laras; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test the influence of companyâs characteristic on voluntary disclosure and its implications to the asymmetric information. The research is divided into two parts. The first part of the research is to test the influence of companyâs characteristic to the voluntary disclosure. The second part of the research is to test the influence of voluntary disclosure to the asymmetric information.This research is carried out by using two regressions analysis models. The first model is done by using multiple linear regressions in order to test the influence of the companyâs characteristic to the voluntary disclosure. The second model is done by using simple linear regressions in order to test the influence of voluntary disclosure to the asymmetric information on the company. The sample of the research is the annual reports of the manufacturing companies which are listed on Indonesia Stock Exchange in 2011-2013 periods. 135 annual reports are used as the sample of the research. The result of the research shows that in the first regressions model, the characteristics of the company consist of public stock ownership portion, listing age, firm size, and profitability have influence to the voluntary disclosure which has been made by the company. Other variables which are the liquidity and the size of Public Accountant firm do not have any influence to the voluntary disclosure. On the second regressions model, the result of the research shows that the voluntary disclosure has negative influence to the asymmetric information. Keywords: Characteristic of The Company, Voluntary Disclosure, Asymmetric Information.